Investigation of Risk Factors Associated with the Frequency of Antibodies against Babesia bovis and Babesia bigemina in Cattle in Southern Mozambique - António A. M. Tembue; Cleber O. Soares; Adivaldo H. Fonseca (Research Aspects in Agriculture and Veterinary Science Vol. 2, 2021)
Bovine babesiosis is a disease caused by Babesia spp., a protozoan transmitted by ticks of the Ixodidae family, being a disease of economic importance for cattle in the tropics. In Mozambique it is transmitted by ticks of the species Rhipicephalus microplus, R. decoloratus, R. everts everts, and Hyalomma marginatum rufipes and mainly caused by B. bigemina and B. bovis. The disease is characterized by presenting high rates of morbidity and mortality in countries of tropical and subtropical climates, and is widespread in southern Mozambique, where most livestock is made up of beef cattle imported from neighboring countries. This study aimed to investigate gender, age and geographical origin as risk factors associated with serological prevalence and molecular diagnostic of B. bigemina and B. bovis in beef cattle in the provinces of Maputo, Gaza and Inhambane, southern Mozambique, through indirect enzyme-linked immunosorbent assay (i-ELISA) and polymerase chain reaction (PCR). A total of 809 and 240 blood samples from cattle were randomly collected and analyzed simultaneously by i-ELISA and PCR. The overall prevalence of B. bigemina and B. bovis was 71.8% (n = 581) and 76.6% (n = 620), by i-ELISA and 11.3% (n = 27) and 37.1% (n = 89) by PCR test, respectively. Significant difference in the two infections was observed according to age and geographical origin of the samples. The results of this research provide valuable information on the epidemiology of infection with B. bigemina and B. bovis in beef cattle in the region studied, which can be used by domestic livestock managers in planning future interventions in this disease control programs.